2019
DOI: 10.9734/ejnfs/2019/v9i330067
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Antioxidant Potential in Thermally Processed, Underutilized Food Grains of the Himalayan Region

Abstract: Aims: To determine the bioactive components and total antioxidant capacity (TAC) in selected underutilized crops of the Himalayan region viz. Barnyard millet, Grain amaranth, Rice bean, Black soybean and Horsegram. Study Design: Experimental design (Lab experiment). Place and Duration of Study: Department of Foods and Nutrition, College of Home Science, G. B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand, in the year 2016-18. Methodology: We applied different processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Extraction of bioactive components found in the optimized extruded snack was carried out following the method given by Dutta et al (2019) with slight changes. Extruded snack sample weighing (1.5 g) was extracted with 85% aqueous methanol and acidified to pH 2.0 with 6 N HCL by stirring in a magnetic stirrer for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction of bioactive components found in the optimized extruded snack was carried out following the method given by Dutta et al (2019) with slight changes. Extruded snack sample weighing (1.5 g) was extracted with 85% aqueous methanol and acidified to pH 2.0 with 6 N HCL by stirring in a magnetic stirrer for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the flavonoids remain stable during extrusion cooking (Patil et al, 2016), which may be the reason for the flavonoid retention in this study. Besides, the high flavonoid content of extruded snack may be due to the flavonoids found in barnyard millet (Dutta et al, 2019) and Indian gooseberry (Filipiak-Szok et al, 2012).…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another similar study has shown that the loss of vitamin C in pressure cooking was more as compared to open pan cooking of cabbage and Ethiopian green collard (Hailemariam and Wudineh, 2020). Dutta et al (2019) has suggested that millets are rich in micronutrients and provide a balanced diet if consumed in an adequate amount. The study also implies that bioactive components (phenolic and flavonoids) of millets reduce as the temperature and pressure increases (Figure 1-E).…”
Section: Nutrients Loss Due To Pressure Cookingmentioning
confidence: 99%